Return and Volatility Linkages among G-7 and Selected Emerging Markets - Bhuyan, Rafiqul (2015)
In this research, using twelve year daily data on sixteen market indicies, we examine the return and volatility linkages among developed and selected emerging stock markets. All markets exhibit excess kurtosis and ARCH effect in addition to non-normality. Our results show the existence of non-normality, excess kurtosis and excess volatility (ARCH effect) in all markets. There is also a positive pair-wise correlation among these markets. Interesting observation is that the daily volatility of Indonesia, among all markets including G-7 markets, is observed to be the smallest and there is negative correlation between Hong Kong and China Markets during the sample period. We find that these markets are highly linked except for Italy. Further to our analysis, we observe that except for China, all these markets also exhibit leverage effects. We also observe the asymmetry in volatility in all markets, except for China. Volatility transmission among equity markets in the same continent have the most influence for the stock markets in that area, except for UK market that has links to the USA stock markets. Results also indicate portfolio mix for investors of any country is different from another country.